(untitled) (Fiep Bulletin - online, 2011)
Physical education has taken on a selective basis, excluding those students labeled "less able", regardless of level of education where they are. We work with students toward the adequacy and compliance to standards and expectations set by the schools, which, however, do not take into account its characteristics as a group. The curriculum of the school divided into three areas of knowledge aims to develop student’s skills and abilities; integrated and contextualized. This article derives from a reflective analysis done by years of professional practice and monitoring of trainees of Physical Education in schools. Physical education in the area of Languages, Codes and their technology focuses on the evaluation of practices, promoting the culture of body movement and the relationship of physical education with health and quality of life, considering the skills, abilities, knowledge and attitude of students. The objective complexity takes students and teachers to think, to structure and develop processes to solve complex mental responses.